Effectiveness of Community Based Interventions on Stroke Risk and Psychological Distress in Elderly Patients with Hypertension: A Systematic Review - Ahmad Syauqi Mubarok; Sri Iswahyun; Judge Anasulfalah; Aris Widiyanto; Joko Tri Atmojo; Alfian Muhajir; Holy Charisma Noviyanti (Universitas STRADA Indonesia, 2026)
Hypertension is a major risk factor for stroke and is closely associated with increased psychological distress among older adults. Community based interventions have emerged as a promising strategy to address both conditions simultaneously. However, current evidence regarding their effectiveness from randomized clinical trials remains to be systematically synthesized. To evaluate the effectiveness of community-based interventions on stroke risk and psychological distress (anxiety and depression) among older adults with hypertension. This systematic review was conducted in accordance with the PRISMA 2020 guidelines. Literature searches were performed in PubMed/MEDLINE, Scopus, Cochrane Library, and CINAHL databases. Inclusion criteria comprised randomized controlled trials (RCTs) or quasi experimental studies involving older adults (≥60 years) with hypertension, community-based interventions, and outcomes related to stroke risk and/or psychological distress, published between 2019 and 2024. Exclusion criteria included systematic reviews, meta-analyses, scoping reviews, literature reviews, and observational studies. Study quality was assessed using the Critical Appraisal Skills Program (CASP) checklist for cohort studies and RCTs. Of the 3,247 records identified, 9 studies met the inclusion criteria, involving a total of 35,206 participants. The evaluated interventions included community based physical activity programs, coordinated community clinic care models, multicomponent behavioral interventions, stroke health education, intensive blood pressure controlled by non-physician health workers, and community based cognitive behavioral therapy. All included studies reported significant reductions in systolic blood pressure (mean reduction ranging from 8–15 mmHg). Six studies demonstrated significant reductions in stroke risk (OR 0.64–0.82). Five studies assessing psychological distress reported significant decreases in anxiety and depression scores following the interventions. Community based interventions are effective in reducing stroke risk and psychological distress among older adults with hypertension. Multicomponent approaches integrating blood pressure management, health education, and psychological support produced the most favorable outcomes. These findings support the implementation of integrated community-based programs within primary healthcare systems.